Screening for Depression and Other Psychological Problems in Diabetes A Practical Guide - Lloyd, Cathy E.; Pouwer, Frans; Hermanns, Norbert; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Current epidemiological evidence suggests that at least one third of people with diabetes suffer from clinically relevant depressive disorders which often go unrecognized and untreated.  Research also shows that people with depressive disorders have an increased risk of developing Type 2 diabetes. Furthermore, the prognosis is poorer for either disease when they are co-morbid than when they occur separately. Co-morbid depression and diabetes has a huge impact on quality of life and diabetes management, and is an important public health problem.  While there are many screening instruments available to identify individuals who may have depression, selecting the most appropriate tool for use in a busy diabetes clinic or primary care setting may not be straightforward.   Screening for Depression and Other Psychological Problems in Diabetes: A Practical Guide provides an up-to-date overview of available instruments for screening for depression in diabetes. The book reviews the most commonly used screening tools and considers their utility in a range of settings and countries. Guidance on the practical use of each tool is also provided. Other psychological problems found to be common in people with diabetes as well as diabetes-specific emotional difficulties are also considered.   This book will appeal to a range of health care practitioners caring for people with diabetes, including diabetologists, general practitioners, practice nurses and diabetes specialist nurses. The issues considered here are applicable to all diabetes populations across the world and thus this book will appeal to a broad international readership as well as to researchers in the field of diabetes and mental health.
1. Why and when should we screen for depression and other psychological problems? -- 2. Disentangling Clinical Depression from Diabetes-Specific Distress: Making Sense of the Mess We’ve Made -- 3. Key concepts in screening for depression in people with diabetes -- 4. Cultural applicability of screening tools for measuring symptoms of depression -- 5. Top Ten Screening Tools for measuring depression in people with diabetes -- 6. Measuring depression in children and young people -- 7. Screening for depression in older people -- 8. Screening for depression in people with diabetes in primary care -- 9. Screening in Secondary care -- 10. Measuring and assessing depression in people with diabetes: implications for clinical practice.
Keywords: Diabetes; Psychiatry; Endocrinology .; Diabetes; Psychiatry; Endocrinology